2018
DOI: 10.1111/dom.13502
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of healthcare resource utilization and costs in patients with type 2 diabetes initiating dapagliflozin versus sitagliptin

Abstract: Patients who initiated DAPA or SITA had similar all-cause and diabetes-related healthcare costs over 1 year of follow-up. In the subgroup of patients treated with OAD monotherapy at baseline (84% metformin monotherapy), those who initiated DAPA as add-on therapy had lower costs than patients who added SITA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…A smaller study using US data (n = 5444) that compared healthcare costs related to initiation of either dapagliflozin or sitagliptin reported similar findings, despite using a different methodology and using data from a country with a different healthcare infrastructure (eg, more than three‐fold healthcare costs and insurance‐based healthcare than in the present study) . They also concluded that the lower hospital healthcare cost associated with dapagliflozin treatment was offset by the higher drug costs .…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…A smaller study using US data (n = 5444) that compared healthcare costs related to initiation of either dapagliflozin or sitagliptin reported similar findings, despite using a different methodology and using data from a country with a different healthcare infrastructure (eg, more than three‐fold healthcare costs and insurance‐based healthcare than in the present study) . They also concluded that the lower hospital healthcare cost associated with dapagliflozin treatment was offset by the higher drug costs .…”
Section: Discussionsupporting
confidence: 64%
“…They also concluded that the lower hospital healthcare cost associated with dapagliflozin treatment was offset by the higher drug costs . The present study evaluated a larger, well‐matched population (based on 96 clinical and cost variables at baseline, using propensity score matching) with a longer duration of follow‐up, thus providing important additional detailsed insights beyond those from the US study …”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations